Personality Contribution to Employees Performance at Dinas Lingkungan Hidup dan Kebersihan Kota Kupang - Tien Yustini; Jefirstson Richset Riwukore; Marzuki Alie; Asmawati; Katharina Yulita Kana (Institute of Computer Science (IOCS), 2022)
This research aimed to analyze and prove the influence and contribution of personality on employee performance using the dimensions of neuroticism, extroversion, and conscientiousness. This research was conducted in April 2022 at the Dinas Lingkungan Hidup and Kebersihan Kota Kupang. This research is classified as quantitative research. The research population was 172 employees whose sample was determined by simple random sampling using the probability sampling technique with the Slovin method at a probability of 5% so that the sample of respondents was as many as 120 employees. The types of data used are primary and secondary data obtained by questionnaire, observation, and documentation techniques. Data analysis used multiple linear regression analysis. The results showed that the neuroticism variable had a negative and significant effect on employee performance because it had a t-count < t-table (-3.670 < 1.98027) on sig. 0.000 < 0.05. The extroversion variable positively and significantly affect employee performance because the t-count > t-table (3.781 > 1.98027) on sig. 0.000 < 0.05 and the conscientiousness variable has a positive and significant effect on employee performance because the t-count > t-table (9.226 > 1.98027) on sig. 0.000 < 0.05. Simultaneously, the variables neuroticism, extroversion, and conscientiousness have a positive and significant effect on employee performance because of the F-count > F-table (64.957 > 2.68) at sig. 0.000 < 0.05. The contribution of the independent variables to the dependent variable sequentially from the highest to the lowest, namely conscientiousness of 0.433 units, extroversion of 0.205 units, and neuroticism of -0.187 units. The managerial implication of the research shows that the implementation of the personality of the employees at the Dinas Lingkungan Hidup and Kebersihan Kota Kupang affects employee performance positively and significantly.